2021
DOI: 10.17691/stm2021.13.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Fragmentation of Urinary Stones as a Method of Preventing Inflammatory Infections in the Treatment of Urolithiasis (Experience in Successful Clinical Use)

Abstract: The introduction of technologically advanced methods of lithotripsy into medical practice changes the nature of postoperative complications. Among them, the main complications are inflammatory infections. This largely determines the search for new, improved methods of stone fragmentation avoiding small stone fragments and dissemination of the pelvicalyceal system of the kidney with stoneassociated infection. The authors have developed a method for controlled stone fragmentation using a continuous-wave diode la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 24 Additionally, it has been shown that the prevalence of common infectious complications in patients following urinary stone surgery, including fever and systemic inflammatory response syndrome (SIRI), could be as high as 27.4%. 25 Given the above clinical characteristics of urinary stone, we deem older patients undergoing urinary calculi surgery might be at high risk for POD, and it is crucial to identify its associated risk factors for preventing POD. Nevertheless, to our knowledge, the POD incidence and potential risk factors among older adults after urinary calculi surgery have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Additionally, it has been shown that the prevalence of common infectious complications in patients following urinary stone surgery, including fever and systemic inflammatory response syndrome (SIRI), could be as high as 27.4%. 25 Given the above clinical characteristics of urinary stone, we deem older patients undergoing urinary calculi surgery might be at high risk for POD, and it is crucial to identify its associated risk factors for preventing POD. Nevertheless, to our knowledge, the POD incidence and potential risk factors among older adults after urinary calculi surgery have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…A complex of metaphylactic measures, such as lifestyle changes, hyperhydration, dietary modifications, correction of concomitant diseases and hormonal disorders, is considered extremely important to prevent relapses after surgical treatment. In addition, the prevention of postoperative recurrence depends on minimizing intraoperative trauma, reducing the risk of infectious complications, and avoiding residual fragments that can act as initial nucleus of stone formation (6). It is important to note that the recommendations for stone treatment have been changed in the context of the pandemic.…”
mentioning
confidence: 99%